Public Sector Financial Reforms and Performance of Government Entities in Nigeria - Oluwagbade, Oluyinka Isaiah; Jimba, Kareem Isiaka; Dauda, Folorunsho Quadri; Boluwaji, Olayinka Dominion; Abe, Temitope Adedayo (International Journal of Economics and Financial Issues, 2024)
A few scholars have remarked that public agencies in Nigeria are typified by corrupt activities, as well as a slew of other issues. Surprisingly, despite the fact that all succeeding Nigerian politicians and bureaucrats also acknowledge that corruption is a barrier to national growth, the bulk of them assume office as doctors but exit as patients. As a result, Nigerian Government has introduced various economic reforms to boost the performance of government entities in the country. Therefore, this study examined the effects of public sector financial reforms on performance of government entities in Nigeria. Specifically, this study examined the effects of anti-graft reforms, information technology based reforms and financial planning reforms on performance of government entities in Nigeria, The study employed survey research design to collect data from 306 personnel across 188 Ministries, Departments and Agencies (MDA) in Nigeria. Ordered logistic regression and ordinary least square (OLS) regression were employed for data analysis. The study found that anti-graft reforms (Anti-Graft agencies), information technology based reforms (IPPIS and GIFMIS), and financial planning reforms (Budgetary control) significantly enhanced the financial performance of government entities in Nigeria. Likewise, the study revealed that anti- graft reforms (Anti-Graft agencies), information technology based reforms (IPPIS), financial planning reforms (Budgetary procedure) and financial reporting reforms (IPSAS) had significant positive effects on non- financial performance of government entities in Nigeria. Overall results revealed that anti-graft reforms (Anti-Graft agencies, anti-graft legal framework), information technology based reforms (IPPIS and GIFMIS), and financial planning reforms (Budgetary procedure) significantly boosted the financial performance of government entities in Nigeria. The study concluded that public sector financial reforms boosted the performance of government entities in Nigeria, and recommended that the Nigerian government strengthen the agencies implementing public sector financial reforms to boost the performance of government entities better.